Morphological evaluation of an in situ collection of species from the Annonaceae family in Colombia (2016)
An in situ collection composed of 167 accessions of the species Annona cherimola, A. glabra, A. reticulata, and A. squamosa, Rollinia sp., and the interspecific hybrid A. squamosa × A. cherimola was established through bioprospecting of genetics resources of the Annonaceae family in the Colombian Andean and Caribbean regions. These accessions were distributed in 13 departments and 48 municipalities. The most representative species of this collection are A. squamosa and A. reticulata, which are derived from traditional cultivars of populated centers with a variable altitude range of up to 1,021 m a.s.l. The morpho-agronomic evaluation was carried out on 98 accessions using 25 qualitative and quantitative descriptors, which identified the phenotypic traits in A. squamosa and A. reticulata that are related to fruit quality, such as size, weight, symmetry, degrees Brix, pH, acidity, seed weight and seed number, which are the more discriminating descriptors, differentiating six clusters in A. squamosa and four clusters in A. reticulata.